Treatment of ovarian cyst after clomiphene citrate ovulationinduction - Mahmood Yaseen, Enas (Tikrit Journal of Pharmaceutical Sciences, 2023)
Infertility is a commen problem around the world . About one in six of all couples have some problem in getting pregnant and that includes some trying for a second or subsequent baby!) . The most common causes of it is ovulation defects and the famous treatment of this cause is by ovulation induction drugs especially clomiphene citrate which used for long period , but this treatment is not without side effects and one of the side effects is ovarian cyst . The aim of this study is to assess the effect of oral contraceptive pills , provera tablets (medroxyprogesterone acetate tablets) and expectant management in the resolution of ovarian cysts induced by clomiphene citrate ovulation induction Study design : a prospective randomized study Setting: patients complained of ovarian cyst more than 2.5 mm were diagnosed by ultrasound after clomiphene citrate ovulation induction and randomized into 3 groups . Group ( !) received oral contraception , group ( 2) received oral progesterone tablets treatment and group ( 3) had expectant management. Follow up of patients were done monthly by ultrasound and resolution of cyst was observed as a main out come measure .